Novel UWB communication pulse design method - LIN Zhi-yuan; WEI Ping (Tongxin xuebao)
Based on the restriction of federal communications commission （FCC） emission mask, the methods of design- ing impulse pulse waveforms for ultra wideband （UWB） communications was investigated. The second derivative Gaus- sian pulse with the diverse shaping factors and the diverse spectral moving factors acted as basis functions. The iterative combination pulse method and the linear minimum mean square error （LMMSE） combination pulse method were pre- sented. The comparison were presented for the bit error rate （BER） performance analyses of the pulse position modula- tion time hopping ultra wideband （PPM TH UWB） impulse radio （IR） communication system employing the iterative combination pulse or the second derivative Gaussian pulse in the additive white Gaussian noise （AWGN） channel, multi- ple user interference （MUI） and multiple path channel. Several numerical experiments demonstrate the efficiency of this method.